Interventions including a nutrition component aimed at managing gestational weight gain or postpartum weight retention: a systematic review and meta-analysis. (March 2019) - Vincze, Lisa; Rollo, Megan; Hutchesson, Melinda; Hauck, Yvonne; MacDonald-Wicks, Lesley; Wood, Lisa; Callister, Robin; Collins, Clare
ABSTRACT: Objectives: The objective of this systematic review was to evaluate the effectiveness of interventions that include a nutrition component aimed at improving gestational weight gain and/or postpartum weight retention. Introduction: Excessive gestational weight gain and postpartum weight retention increase the risk of adverse maternal and neonatal outcomes. Current evidence comprises many interventions targeting gestational weight gain and postpartum weight retention that incorporate a nutrition component. To date, no review has synthesized evidence from pregnancy through the postpartum period or described the intervention approaches in detail. Inclusion criteria: The review included women (≥18 years) during pregnancy and/or up to 12 months postpartum. Studies were included if they involved a weight management intervention with a nutrition component and had the primary objective of determining the impact of gestational weight gain and/or postpartum weight change. Interventions were compared to usual care (i.e. control conditions with no intervention or wait-list control or standard pregnancy or postpartum care) or "other" (alternative intervention). The review considered randomized controlled trials published between 1980 and January 21, 2016. Studies that included a weight related primary outcome measured during pregnancy and/or postpartum were included. Methods: Seven databases were searched and the reference lists of included studies were searched for additional studies not previously identified. Two independent reviewers assessed the methodological quality of studies using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI SUMARI). The JBI SUMARI standardized data extraction tool was used to extract data. A narrative synthesis was undertaken to qualitatively synthesize included studies, with meta-analyses used to pool weight outcome data from studies conducted separately for pregnancy and postpartum. Effect sizes for meta-analyses have been expressed as weighted mean differences (95% confidence intervals). Results: The search yielded 4063 articles of which 48 articles from 39 studies were included. Eleven of 20 studies during pregnancy reported significant reductions in gestational weight gain with the intervention when compared to control groups. One of five studies where the intervention was conducted during both pregnancy and postpartum reported statistically significant reductions in gestational weight gain, and postpartum weight retention between intervention and control groups. Nine of 14 studies conducted after childbirth reported statistically significant intervention effects, indicating lesser postpartum weight retention. Random effects meta-analyses indicated that despite considerable heterogeneity, interventions conducted during pregnancy (−1.25 kg; 95% CI: −2.10 kg, −0.40 kg; p = 0.004), and postpartum (−3.25 kg; 95% CI: −4.69 kg, −1.82 kg; p < 0.001) were significantly more effective at improving weight outcomes compared to usual care or other interventions. Most studies were of moderate quality due to lack of clarity in describing study details required for appraising methodological quality. Few interventions were conducted from pregnancy through the postpartum period (n = 5). Limited interventions adopted online modalities in intervention delivery (n = 4). Intention-to-treat analysis was used in only 12 studies. Conclusions: The pregnancy and postpartum period presents a unique opportunity to engage women in interventions to help optimize lifestyle behaviors for weight management, however the optimal approach is unclear. Improving consistency in intervention implementation and reporting will improve future evidence synthesis.